Crystallization and preliminary X-ray diffraction analysis of the DNA-binding domain of the response regulator SaeR from Staphylococcus epidermidis - Chen, Sheng-Chia (International Union of Crystallography, 2013)

(untitled)
SaeR is the response regulator of the SaeRS two-component signal transduction system, which is involved in regulating bacterial autolysis and biofilm formation. SaeR comprises an N-terminal receiver domain and a C-terminal effector domain. The effector domain possesses DNA-binding and transactivation functions. Here, the effector domain of SaeR from Staphylococcus epidermidis was purified and crystallized using the sitting-drop vapour-diffusion method. The crystals diffracted to a resolution of 2.15 Å and belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 34.20, b = 53.78, c = 111.66 Å. Determining the structure will provide insights into the mechanisms underlying DNA binding.